Negotiating Indigenous benefits from payment for ecosystem service (PES) schemes. (May 2016) - Robinson, Cathy J; James, Glenn; Whitehead, Peter J
Highlights: Indigenous people's relationships to their traditional estates, and the practices involved in their care, can inform the design of payment for ecosystem service (PES) agreements. We expand understandings and applications of cultural ecosystem services to show how this can build synergies between PES frameworks and the priorities of Indigenous groups. Indigenous savanna landscape burning is used as an illustrative example to demonstrate how this framing can be applied to designing and assessing Indigenous benefits from PES agreements. Abstract: This paper draws on research conducted with Aboriginal land managers across Northern Australia to show how and why payments for ecosystem service (PES) schemes should be framed around Indigenous rights to and relationships with their traditional estates. PES schemes offer opportunities to recognize and support Aboriginal communities' land and sea management knowledge and practices, and there is strong evidence that Indigenous communities are seeking to engage with such schemes. We focus on Aboriginal savanna landscape management, particularly traditional burning practices, to extend the ecosystem services framework to recognize Indigenous values and interactions with their lands as a critical service for Indigenous well-being. Drawing on case-study analysis of PES projects negotiated to support Aboriginal fire management programs across Northern Australia, we show how cultural ecosystem services can be applied to represent the active, dynamic and often interdependent relationships inherent in Indigenous human-environment relationships.